CENTRIPETAL MOVEMENT OF THE CAPILLARIES IN THE CENTRAL MACULAR REGION AFTER INTERNAL LIMITING MEMBRANE PEELING. Issue Volume 13:Issues 1(2019) (2019) - Kumagai, Kazuyuki; Hangai, Masanori; Furukawa, Mariko; Suetsugu, Tetsuyuki; Ogino, Nobuchika
Abstract : Purpose: To report a case that showed centripetal movements of the capillaries in the central macular region after vitrectomy with internal limiting membrane peeling. Methods: A 57-year-old pseudophakic woman underwent successful vitrectomy with internal limiting membrane peeling and air tamponade for a vitreomacular traction. Optical coherence tomography angiographic images of the 3 mm × 3 mm inner retinal vascular plexus were examined preoperatively and at 3 months postoperatively. The changes in 93 corresponding bifurcations of the capillaries were assessed. Results: The majority of the bifurcations were displaced towards the fovea at 3 months after the vitrectomy with internal limiting membrane peeling. Conclusion: Optical coherence tomography angiography was used to help visualize the centripetal movement of the inner retina around the fovea after the vitrectomy with internal limiting membrane peeling. Abstract : Vitrectomy with internal limiting membrane peeling was performed on a patient with a vitreomacular traction. Optical coherence tomography angiographic images recorded preoperatively and postoperatively showed movements of the capillary bifurcations after internal limiting membrane peeling indicating a centripetal movement of the inner retinal layers.